HUBUNGAN PERHATIAN ORANG TUA DAN CARA BELAJAR DENGAN PRESTASI BELAJAR AKUNTANSI SISWA KELAS X JURUSAN AKUNTANSI SMK MUHAMMADIYAH 2 BANDAR LAMPUNG - Zainal, Vetri Yanti (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The study aims to determine the relationship between parental attention and learning styles to the students’ learning achievement of Accounting of SMK Muhammadiyah 2 Bandar Lampung. This study uses correlation survey method. The population in this study were all students of class X in Accounting totaling 45 students. The sample used in this study came from all population.Research results revealed that (1) there is a positive and significant relationship between parental attention and learning achievement of Accounting class at the tenth grade students of SMK Muhammadiyah 2 Bandar Lampung. (2) there is a positive and significant relationship between learning style and academic achievement of Accounting class at the tenth grade students of SMK Muhammadiyah 2 Bandar Lampung. (3) there is a positive and significant correlation between parental attention, learning style and the learning achievement of class X Accounting class at the tenth grade students of SMK Muhammadiyah 2 Bandar Lampung.